Poster 2010: A study assessing the safety and efficacy of subcutaneous immunotherapy with a dust mite vaccine with the adjuvant l-tyrosine in a highly sensitized population in a Latin-American city (2014)
In Medellín-Colombia dust mite allergy is prevalent with high intensity of sensitization. We intended to describe the tolerability and efficacy of a new vaccine with a new adjuvant L-tyrosine in this population.